One Hundred Years of History and a Few Solitudes - Bryce, Benjamin (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2023)
This introductory article reflects on the centenary of the journal and explains the goals of this issue that seeks to analyze one hundred years of historiographic developments in more than a thousand articles. It presents insights about how the journal developed, particularly in the early decades, and what remnants of the early decades are still with us.